Is Shame Morally Relevant to Ecological Ethics? - Klimková, Andrea (Studia Ecologiae et Bioethicae, 2023)
In recent years, we have seen a resurgence of the topic of shame in philosophy and moral philosophy. The paper analyses shame as a moral emotion in contemporary moral-philosophical and environmental discourse. Questions are articulated, in which different contexts shame has already been studied and which of them appear to be crucial for ethics and applied ethics? In the article, the author addresses the concept of environmental shame by Sarah E. Fredericks (2021) and considers the questions: is/can shame be ethically relevant for the cultivation of our attitudes in relation to the environment? Is Shame morally relevant to Ecological Ethics? Can the experience of shame affect our moral judgement, decision-making and action regarding the man-nature relationship? Despite the differences in the understanding of shame as a self-conscious emotion or as a social emotion, in the paper the author argues that environmental shame can have an important preventive function as well as a transformative power for the cultivation of our moral beliefs and attitudes.